Applied techniques for residual oil recovery from source rocks: A review of current challenges and possible developments - Abdulkareem, F.A. (Wiley-Liss Inc., 2021)
Depleted fossil fuel resources have led to an investigation of other promising alternatives such as renewable and unconventional energy sources. Shale formations have limited permeability. Therefore, several extraction techniques have been applied to improve residual oil recovery and production. In this work, the techniques applied above ground to extract the organic fractions from oil/gas shale are discussed. Studies related to compositional fractionation, ultrasonic-assisted, microwave-assisted, supercritical fluids, and surface retorting techniques have been conducted systematically in approximately 150 scholarly articles over the past 10 years. The impacts of each technique as well as the drawbacks and challenges are highlighted in this paper. The fractionation techniques are sufficient in general; however, they are time consuming as they include several stages and use a considerable amount of solvents. Ultrasonic and microwave techniques are highly reliant on formation transparency linked to the organic fraction heterogeneous distribution. The surface retorting method, which is highly efficient with up to 90 recovery, for example, the Galoter and Paraho methods, is still dependent on shale particulate size, generates a massive amount of spent shale as waste, and is prominently emissive. Therefore, assessments that can be used to overcome existing drawbacks are considered. This can provide practical insight about these techniques to overcome limitations and concerns in terms of efficiency, cost, environmental issues, and reliability features. The work highlights the dominant extraction techniques for further development. Â© 2020 Canadian Society for Chemical Engineering